Nuclear Matrix Protein SMAR1 Represses c-Fos-mediated HPV18 E6 Transcription through Alteration of Chromatin Histone Deacetylation - Chakraborty, Samik (American Society for Biochemistry and Molecular Biology, 2014)
Matrix attachment region (MAR)-binding proteins have been implicated in the transcriptional regulation of host as well as viral genes, but their precise role in HPV-infected cervical cancer remains unclear. Here we show that HPV18 promoter contains consensus MAR element in the LCR and E6 sequences where SMAR1 binds and reinforces HPV18 E6 transcriptional silencing. In fact, curcumin-induced up-regulation of SMAR1 ensures recruitment of SMAR1-HDAC1 repressor complex at the LCR and E6 MAR sequences, thereby decreasing histone acetylation at H3K9 and H3K18, leading to reorientation of the chromatin. As a consequence, c-Fos binding at the putative AP-1 sites on E6 promoter is inhibited. E6 depletion interrupts degradation of E6-mediated p53 and lysine acetyl transferase, Tip60. Tip60, in turn, acetylates p53, thereby restoring p53-mediated transactivation of proapoptotic genes to ensure apoptosis. This hitherto unexplained function of SMAR1 signifies the potential of this unique scaffold matrix-associated region-binding protein as a critical regulator of E6-mediated anti-apoptotic network in HPV18-infected cervical adenocarcinoma. These results also justify the candidature of curcumin for the treatment of HPV18-infected cervical carcinoma.